UJI EFEKTIVITAS EKSBIMA SEBAGAI SUBTITUTOR SIDABAS 500 SC TERHADAP HAMA THRIPS (Thrips sp) PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Sri Utami; Mochamad Soeprijadi Djoko Laksana (Florea : Jurnal Biologi dan Pembelajarannya, 2015)
Research to determine the effectiveness of the extract against diseases curly terms of cure rates and yields of crops cayenne pepper (Capsicum frutescens l.) In Kedung Padang District of Rejoso Nganjuk. Target outcomes in the form of (1) Product insecticide mahogany seed, (2). Increased yields cayenne pepper. (3). Decrease the use of chemical insecticide. The results are used by farmers as subtitutor sidabas or other insecticides. The study used an experimental method with randomized block design Randomized Complete Block Design or (RCBD) which consists of 5 levels of treatment and four replications (4 blocks). Applied research in the area of 2500 m2 chili. 5 levels of treatment are: A = with insecticide mahogany 75 cc / 14 l of water., B = with insecticide mahogany 100 cc / 14 l of water, C = with insecticide mahogany 200 cc / 14 l of water, D = with insecticide mahogany 150 cc / 14 l of water, E = with chemical insecticides Sidabas 500 SC. The results showed that treatment with insecticide mahogany D 150 cc / 14 liters of water, produces cure rates of disease, most notably curly 91.41% and yield the greatest 174 kg. E treatment with chemical insecticides sidabas 500 SC provides 64.84% cure rate and yield 127 kg. This means insecticide mahogany 150 cc / 14 liters of water is more effective than sidabas 500 SC